2023
DOI: 10.1111/jocd.15584
|View full text |Cite
|
Sign up to set email alerts
|

Topical management of acne scars: The uncharted terrain

Abstract: Majority (80%-90%) of patients who develop acne scars have atrophic scars associated with loss of collagen compared to a minority who show hypertrophic scars and keloids. 1 Loss of dermal matrix in the form of collagen breakdown during the inflammatory stage leads to atrophic scars. The ratio of MMPs (Matrix Metalloproteinases) to tissue inhibitors of MMPs determines the development of atrophic or hypertrophic scars. Inadequate deposition of collagen leads to formation of an atrophic scar while, if the healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…In fact, this study supports the hypothesis that hydration or water impermeability may be responsible for its effective healing results and the inhibition of fibroblasts proliferation, together with inhibition of collagen and glycosaminoglycan production in the hydrated group and no apparent change in fibroblast activity in the silicone-treated group [90]. Silicone also causes immunological alterations, namely downregulating fibrogenic cytokine TGFβ2 [91], TGF-β [92], or increasing basic fibroblast growth factor and IL-8 levels [93,94]. Since silicone is inert, it is not capable of inhibiting microbial growth, but it can act as a bacterial barrier [81].…”
Section: Siliconessupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, this study supports the hypothesis that hydration or water impermeability may be responsible for its effective healing results and the inhibition of fibroblasts proliferation, together with inhibition of collagen and glycosaminoglycan production in the hydrated group and no apparent change in fibroblast activity in the silicone-treated group [90]. Silicone also causes immunological alterations, namely downregulating fibrogenic cytokine TGFβ2 [91], TGF-β [92], or increasing basic fibroblast growth factor and IL-8 levels [93,94]. Since silicone is inert, it is not capable of inhibiting microbial growth, but it can act as a bacterial barrier [81].…”
Section: Siliconessupporting
confidence: 81%
“…It is also associated with a reduction of mast cell activity, edema, and excessive extracellular matrix formation. Silicone also contributes to the right alignment of collagen deposition by increasing temperature, oxygen tension, and electrostatic properties [81,92].…”
Section: Siliconesmentioning
confidence: 99%
“…The consequential collagen breakdown in this scar subtype is due to the loss of dermal matrix producing the atrophied appearance observed. 5…”
Section: Atrophicmentioning
confidence: 99%
“…Results showed improved texture in the silicone gel application areas. 5 A metastudy of 27 trials showed silicone gel sheeting to be a successful and safe approach. It has shown the ability to improve old scar elasticity in comparison to untreated scars.…”
Section: Acnementioning
confidence: 99%
See 1 more Smart Citation